2017
DOI: 10.1590/1980-5497201700030014
|View full text |Cite
|
Sign up to set email alerts
|

Redistribuição de gordura corporal e alterações no metabolismo de lipídeos e glicose em pessoas vivendo com HIV/AIDS

Abstract: Introduction:The HIV lipodystrophy syndrome is characterized by changes in metabolism, and body composition that increase cardiovascular risk of people living with HIV/AIDS (PLWHA) using highly active antiretroviral therapy (HAART). Objective: To assess the prevalence of lipodystrophy and changes in lipid and glucose metabolism in PLWHA in use of HAART. Methods: For the anthropometric evaluation we measured weight, height and abdominal circumference (AC). For the lipodystrophy evaluation we conducted physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
(28 reference statements)
2
21
1
3
Order By: Relevance
“…Regarding the anthropometric alterations, the prevalence of overweight and increased WC in the present study were lower than those identified in a study by Beraldo et al 14 . in 262 individuals living with HIV/AIDS (51% and 53%, respectively).…”
contrasting
confidence: 93%
“…Regarding the anthropometric alterations, the prevalence of overweight and increased WC in the present study were lower than those identified in a study by Beraldo et al 14 . in 262 individuals living with HIV/AIDS (51% and 53%, respectively).…”
contrasting
confidence: 93%
“…As previously demonstrated HIV patients on HAART presented dyslipidemia characterized by high triglyceride levels and reduced HDL-cholesterol levels [ 49 ]. This result is by previous data that showed that in patients with HIV in use of HAART the most prevalent metabolic alterations were reduced HDL-cholesterol and hypertriglyceridemia [ 4 ]. The association of dyslipidemia with high levels of LPS may contribute to increasing the cardiovascular risk in HIV patients on HAART.…”
Section: Discussionsupporting
confidence: 69%
“…Over the past 20 years, the introduction of antiretroviral therapy has increased the life expectancy of HIV patients, but it also introduced complicating diseases such as cardiovascular events, renal disease, osteoporosis and metabolic alterations [ 1 3 ]. Previous data showed that in patients with HIV in use of HAART the most prevalent metabolic alterations were reduced HDL-cholesterol and hypertriglyceridemia [ 4 ]. Among the metabolic complications encountered, insulin resistance is a central pathophysiological condition that can contribute to the development of diabetes and cardiovascular events [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is also shown to increase, whose effects range from alterations in glucose metabolism to the development of type-2 diabetes mellitus, as reported in the literature 8,20 .…”
Section: Tablementioning
confidence: 69%
“…Lipohypertrophy, or lipomatosis, can occur in more than one region simultaneously and corresponds to the increase in central abdominal fat tissue and in the cervical back, gynecomastia, and enlarged breasts among women. The etiology of lipodystrophy in treated HIV infection is multifactorial 7,8,9 .…”
Section: Introductionmentioning
confidence: 99%